Peranan Bidang DATUN Dalam Memberi Pendampingan Hukum Tentang Ganti Rugi Pengadaan Tanah Untuk Kepentingan Umum (Studi Kejaksaan Tinggi Sumatera Utara) - Argatta Oliver Pratama Hutapea; Ojak Nainggolan (Penerbit Jurnal Indonesia, 2025)
Land is one of the most important sources of life for humans, and one of its main functions is to be used as a place of residence, namely to build houses. In this case, to prevent land resolution from causing problems between government agencies and the community, the Indonesian Attorney General's Office, particularly the High Prosecutor's Office of North Sumatra in the field of Civil and State Administrative Law (DATUN), has fully utilized the authority of state attorneys in civil matters, granted by law and by delegation from a power of attorney. This includes legal assistance, law enforcement, legal considerations, legal services, and other actions. The role of the state attorney is to provide legal assistance to the government and the community in resolving land acquisition for public benefit. Land resolution related to land acquisition for public benefit can be carried out in two ways, namely by forcibly extinguishing rights and through consent. The purpose of this writing is to explain how the Civil and State Administrative Law sectors, specifically the State Attorney, act as legal advisors in the matter of land acquisition for public interest. This includes issues of compensation for land that will be used for public purposes.